Generation of digital terrain models using different geospatial measurement technologies: A comparative analysis of the terrain data sets - Ali Karaca; Ender Buğday (Turkish Journal of Forestry)
Since early civilizations, the growing need for information has driven continuous advancements in surveying and photogrammetry, particularly with modern technologies enhancing measurement techniques and the integration of global positioning systems across terrestrial, aerial, and satellite platforms. Since the early twenty-first century, technologies such as GPS, mobile phones, GNSS-CORS, and UAVs have rapidly become integral to practical measurements across various sectors, including construction, mining, aviation, agriculture, and forestry. In this study, topographic measurement devices with different measurement sensitivities, such as GPS, GNSS-CORS, mobile phones and UAVs, were measured in the same size area and compared in terms of measurement time, precision and mapping. In addition, digital elevation values were calculated for the same area and mapped in the Google Earth software environment from satellite data, a widely referenced remote sensing dataset. These different measurement data obtained were compared on the same plane and as a result, it was determined that GNSS-CORS and RTK-UAV devices with RTK provided high precision data, followed by UAV without RTK device, Google Earth data set, mobile phone and GPS device. Upon examination of the results of this study, it was determined that UAV technology is particularly compatible with research endeavors demanding high precision and rapid data acquisition. Conversely, for studies where high sensitivity is not a primary consideration, measurements derived from GPS and mobile phone data may offer a suitable alternative.